Group Entrepreneurship Among SHG Women: A Study of Selected SHGs in Guntur District, Andhra Pradesh - Vadde, Vishnu; Vijaya Ratnam, N. (Prabandhan: Indian Journal of Management, 2015)
Economic development is possible only with the help of planned and unrelenting business activities. Entrepreneurs are the human agency at the back of such activities. Entrepreneurship is the skill or quality of such human resources, which is snatching opportunities and organizing endeavors for their commercial exploitation. The present study attempted to empirically identify group entrepreneurship development among selfhelp groups in Guntur district of Andhra Pradesh. The study purposively selected the sample respondents as one respondent from the 240 identified SHGs (the total sample size was 240 respondents from 240 groups from two revenue divisions in Guntur district). The study revealed that the government and agencies need to make the necessary changes in implementation of the various revenue generating schemes and need to identify the specific needs of the poor women.